Salybia Bay, North East Trinidad, B.W.I. - Della Costa, H. (Y. De Lima and Co. Ltd., Trinidad, 2009)
A view of Salybia Bay on Trinidad's north east coast show the heavily forested headland in the distance and the sandy beach that line the coast. Postcard number K-5139.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bays--Trinidad and Tobago; Coasts--Trinidad and Tobago; Beaches--Trinidad and Tobago; Men--Trinidad and Tobago; Women--Trinidad and Tobago; Children--Trinidad and Tobago; Girls--Trinidad and Tobago; [1950]